Characterization of seedling and adult plant resistance to stripe rust in recombinant inbred lines derived from wheat landrace PI388222 × Avocet cross. Issue 1 (10th February 2020) - Aman, Yesrab; Khalid, Fatima; Shaukat, Muzaffar; Mahmood, Tariq; Hasan, Syed Wasim; Mirza, Javed Iqbal
Abstract: Stripe rust caused by Puccinia striiformis f. sp. tritici ( Pst ), is a devastating fungal disease of wheat ( Triticum aestivum L.). The best economical technique for disease control is breeding for genetic resistance to stripe rust. To find resistance genes in landrace PI388222 from Pakistan, a segregating population was developed by a cross between PI388222 and susceptible Australian spring wheat line Avocet 'S'. The F2:4 seeds were harvested and seeds were planted in the greenhouse of Washington State University Pullman, to grow F4:5 recombinant inbred lines (RIL). A variable set of seedling reactions were noted when a set of 136 F5 and parental lines were screened with four Puccinia striiformis f. sp. tritici races (PSTv-37, PSTv-40, PSTv-4 and PSTv-51). The great proportion of RILs showed resistant reaction displayed by the RILs was against PSTv-40, for which 85% of the RILs showed resistant reaction, while less resistance to the race PSTv-37 was detected against which the resistance was for only 49% of the RILs. The RIL population was further evaluated at two locations; Palouse Conservation Field Station (PCFS) and Mount Vernon (MV). In MV field, 76% of RILs displayed resistant reaction while 15% of RILs exhibited moderate reaction. About 53% of RILs exhibited resistant reaction to four P. tritici races that were used in glasshouse screening and they were also resistant in field environments at PCFS and MV. This study demonstrates that landrace comprises partial resistance in the range of resistant to moderately resistant lines.